From “Mental/Psychological Disorder” and/or “Individual Pattern of Adaptation” Toward “Developmental Trajectories During the Lifespan” - Donatella R. Petretto; Alessandro Mura; Mattia Vacca; Gian Pietro Carrogu; Luca Gaviano; Riccardo Atzori; Carmelo Masala (Behavioral Sciences)
A general and still open question in clinical psychology is the crucial one: “What is a psychological/mental disorder?”. In the second half of the 20th century and now, the question has been addressed along two different parallel paths/approaches: one path aimed to classify those disorders, also thanks to the development of the international classification manuals (DSM and ICD); another path aimed to describe in what ways those “disorders” manifest themselves in the life of each individual. While the first path used explicitly the word “disorder”, the second one mainly preferred to use the words “pattern of adaptation/maladaptation”. In this brief perspective paper, we will discuss both paths and approaches, according to the perspective of clinical psychology and as a result of a narrative review. We discuss some differences between the two paths, some points of contact between them, and some critical issues. Moreover, we will briefly discuss a third integrative path that may integrate the first two. We then discussed if the third integrative path may increase the strength of both previous ones and overcome their limits, with the aim to support individual patterns of adjustment, prevent “mental/psychological disorder” and empower individuals in coping with adverse life events during all the phases of lifespan.